KAJIAN HISTORIS LEMBAGA PENDIDIKAN ISLAM DI INDONESIA: TINJAUAN KOMPREHENSIF TERHADAP DIMENSI FORMAL, INFORMAL, DAN NONFORMAL - Laili, Nurul; Ashari, M.Yahya (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
This research aims to comprehensively describe the historical development of Islamic educational institutions in Indonesia, through formal, informal and non-formal dimensions. The research method is conducted through a literature study, which includes the exploration of data and information from various sources collected. Reading references for this research include books, magazines, historical documents, and various journals that are in accordance with the topic of discussion, either direct searches to the Library or through internet media. Since this research is categorized as a literature review, the primary data source involves books and research journals. The research findings show that the formal form of education is directly coordinated by the central government to the regions through tiered education, such as: madrasah and Islamic Universities; Informal form of education is through family and environmental education channels whose learning activities are carried out independently; and Non-formal form of education is education that occurs outside school and is not bound by a flexible but structured national curriculum such as: recitation of books, majelis taklim, Al-Qur'an education, diniyah taklimiyah which consists of several levels. Islamic educational institutions in Indonesia have undergone significant transformations in line with social, political and cultural changes. This research makes an important contribution in understanding the dynamics and strategic role of Islamic educational institutions in Indonesia in the development of quality and character human resources